Web-Based Design of Minangkabau Songket Motif Digital Catalog - Muhammad Habib Yuhandri (Journal of Computer Scine and Information Technology, 2022)
Indonesia's richness in culture requires special attention in terms of its preservation, therefore it is important for us to maintain and preserve Songket cloth, especially its motifs which are rich in the philosophy of local wisdom so that they can be passed down to the next generation. Information technology can be used to solve these problems, especially for digital catalogs that can be used to help preserve Songket cloth through digitizing the motifs on each cloth. Through digitization, it will be easy to get information about the shape of the motif, the name of the motif, the philosophy contained in the motif through an application. The purpose of this study was to build a digital catalog system on the WEB-based Minangkabau Songket motif. The development of this system is carried out by means of data collection, system analysis, system design, and system implementation. This system is built using the PHP programming language and MySQL database. The results of this study provide a tool in the form of a Minangkabau Songket Motif Digital Catalog system. The benefits of research provide the development of deep catalog technology to store information related to Minangkabau Songket motifsSongket